A preparation method of BiVO4-ZnPc nanocomposite material

By synthesizing BiVO4-ZnPc nanocomposites in non-coordinating organic solvents, the problems of high energy consumption and long reaction cycles in the prior art are solved, and efficient photocatalytic performance is obtained, especially in oil drilling waste liquid. The degradation effect of organic pollutants has been significantly improved.

CN116139935BActive Publication Date: 2024-12-13CHINA NAT PETROLEUM CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111383812.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-22
Publication Date
2024-12-13
Estimated Expiration
2041-11-22

AI Technical Summary

Technical Problem

The existing preparation method of BiVO4-ZnPc has problems such as high energy consumption, long reaction period and harsh reaction conditions, which limits its efficient preparation and photocatalytic properties on the nanoscale.

Method used

The reaction was carried out by adding bismuth source, oleic acid and oleamine to 10~20mL non-coordinating organic solvent, followed by adding zinc phthalocyanine and concentrated nitric acid, stirring and heating treatment, and finally obtaining ultra-thin two-dimensional by centrifugation and drying. BiVO4-ZnPc nanocomposite, adjust the temperature and ratio to improve the photocatalytic properties of the composite.

Benefits of technology

The preparation process is simple, time-consuming and mild, and the preparation process is achieved, and the efficiency of photocatalytic degradation of organic pollutants is achieved, especially the degradation effect of organic pollutants in oil drilling waste liquid is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116139935B_ABST
    Figure CN116139935B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of semiconductor photocatalytic material preparation and application, and in particular to a method for preparing a BiVO4-ZnPc nanocomposite material, wherein a bismuth precursor, ZnPc, and a vanadium precursor are mixed and dispersed in the same system in a certain order to obtain BiVO4-ZnPc nanocomposite materials of different proportions. The present invention provides a mild, simple, and short-preparation-cycle BiVO4-ZnPc nanocomposite material preparation method, which can effectively solve the problems of harsh reaction conditions and long reaction cycles, can synthesize ultra-thin two-dimensional nanosheets on a nanoscale, rapidly separate photogenerated carriers, react with water and oxygen to generate highly active oxygen free radicals, and greatly improve the performance of photocatalytic degradation of organic pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation and application of semiconductor photocatalytic materials, and in particular to a method for preparing a BiVO4-ZnPc nanocomposite material. Background Art

[0002] Due to the increasingly serious global energy crisis and environmental pollution problems, people urgently need to develop and utilize clean renewable energy. Among them, the photocatalytic degradation technology of semiconductor materials has become a current research hotspot and effective means, showing great potential and becoming one of the most ideal and effective solutions. Therefore, the preparation and development of efficient and stable visible light photocatalytic materials have become a research hotspot in the fields of materials science, chemistry and environmental science. Therefore, studying photocatalytic degradation technology to treat organic pollutants and reduce or eliminate organic pollution to the environment is of great significance for environmental protection. Monoclinic scheelite BiVO4 has a small band gap (~2.4 eV) and strong absorption in the visible light range. In addition, due to slow charge separation, limited visible light utilization and low charge induced reaction efficiency, the photocatalytic activity of BiVO4 is also unsatisfactory. Metal phthalocyanine (MPc) is similar to light chlorophyll with a porphyrin ring, and its conjugated macrocyclic structure is conducive to establishing a size-matched interface with two-dimensional BiVO4. When BiVO4NSs and ZnPc are excited simultaneously under visible light irradiation, the photogenerated electrons in BiVO4CB will rapidly combine with the photoinduced holes in the valence band of ZnPc due to their close band edge positions. It can both extend the absorption of visible light and greatly enhance the separation of charges. In this case, the spatially separated holes in BiVO4 and the electrons on ZnPc will have thermodynamically sufficient energy to initiate redox reactions and enhance the photocatalytic activity.

[0003] At present, the typical preparation method of BiVO4-ZnPc is the ultra-thin nanostructured BiVO4 prepared by the self-assembly method induced by hexadecyltrimethylammonium bromide (CTAB) reported by XieQs group, which provides a feasible way to prepare this morphology. In the single-pot assembly process, hydroxylated BiVO4NSs are first formed, and then the surface hydroxyl-induced polymer ZnPc is assembled to make it uniformly dispersed on BiVO4NSs. Although this method can prepare BiVO4-ZnPc samples with high purity and crystallinity, this method has obvious disadvantages, such as high energy consumption, long reaction cycle and harsh reaction conditions. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a mild, simple and short-cycle preparation method of BiVO4-ZnPc nanocomposite materials, which can effectively solve the problems of harsh reaction conditions and long reaction cycle, and can synthesize ultra-thin two-dimensional nanosheets on the nanoscale, so that photogenerated carriers can be quickly separated and react with water and oxygen to produce highly active oxygen free radicals, thereby greatly improving the performance of photocatalytic degradation of organic pollutants.

[0005] The present invention is achieved by adopting the following technical solutions:

[0006] A method for preparing a BiVO4-ZnPc nanocomposite material, characterized in that it comprises the following steps:

[0007] S1. Add 3~6mmol of bismuth source Bi(NO3)3·5H2O, 6~12mL of oleic acid and 6~12mL of oleylamine to 10~20mL of non-coordinating organic solvent, stir at 185~195℃ for 10~15min, and stop heating.

[0008] S2. Disperse zinc phthalocyanine ZnPc in 3-5 mL of an organic solvent at a molar ratio of 1%-50% compared to Bi(NO3)3, stir for 50-70 min, then add to step S1, and stir at 90-110°C for 4-6 min;

[0009] S3. Add 10-20 mL of water, 4-6 mL of 15-16 M concentrated nitric acid and 9.6-24 mmol of NH4VO3, mix and stir for 5-20 min, and stir at 100-105°C for 60-90 min under a nitrogen atmosphere;

[0010] S4. After cooling to room temperature, 10-20 mL of ethanol was added to remove the lower aqueous solution, and 10-20 mL of water was added to the upper organic phase to emulsify it to a viscous state. After adding 10-20 mL of ethanol to break the emulsification, the lower aqueous solution was removed, and the upper clear liquid was removed by centrifugation. 10-20 mL of n-hexane and 10-20 mL of ethanol were added, and BiVO4-ZnPc nanocomposites of different proportions were obtained by centrifugation and drying.

[0011] The content of zinc phthalocyanine ZnPc in step S2 is 10%.

[0012] The content of zinc phthalocyanine ZnPc in step S2 is 30% or 50%.

[0013] The BiVO4-ZnPc nanocomposite material is in the form of an ultra-thin two-dimensional sheet with a thickness of 2.8-3 nm.

[0014] In the step S1, a bismuth source, oleic acid and oleylamine are reacted under a nitrogen atmosphere.

[0015] The amounts of oleic acid and oleylamine used are the same.

[0016] The non-coordinating organic solvent is octadecene.

[0017] In the step S2, zinc phthalocyanine ZnPc is dispersed in an organic solvent by ultrasonication for 20 minutes.

[0018] The organic solvent in step S2 is dimethyl sulfoxide, ethanol or dichloromethane.

[0019] The drying in step S4 specifically refers to oven drying.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0021] 1. The preparation method of the present invention has the advantages of short time consumption, low reaction temperature and mild conditions. The whole experimental process is easy to operate, has good experimental repeatability, and effectively reduces the preparation cost, which is very suitable for the industrial production of nanocomposites. The BiVO4-ZnPc nanocomposite obtained by this preparation method is an ultra-thin two-dimensional nanosheet, which can greatly improve the performance of photocatalytic degradation of organic pollutants.

[0022] 2. In the present invention, the bismuth source, ZnPc and vanadium source are added in sequence, so that the bismuth source can be well compounded with ZnPc during the process of growing into BiVO4 by reacting with the vanadium source.

[0023] 3. In this preparation method, the temperature and ratio are adjusted, so that a photocatalyst material with a large yield can be obtained quickly, and ZnPc and BiVO4 can be better compounded during the reaction.

[0024] 4. In the present invention, the BiVO4-ZnPc10% synthesized when the ZnPc addition amount is 10% exhibits good photocatalytic performance, which makes the degradation effect of organic pollutants in oil drilling waste liquid better.

[0025] 5. In the present invention, BiVO4-ZnPc30% and BiVO4-ZnPc50% synthesized when the ZnPc addition amount is 30% or 50% have good uniformity of size and smoothness of edges.

[0026] 6. ZnPc is insoluble in water and organic solvents. However, in the present invention, three organic solvents, dimethyl sulfoxide, ethanol or dichloromethane, are selected to disperse ZnPc to the maximum extent by ultrasonic method, and the composite of BiVO4 and ZnPc can be successfully achieved.

[0027] 7. In the present invention, 10-20 mL of ethanol is added to break the emulsion and then the lower aqueous solution is removed, which can better remove the unreacted raw materials and other impurities. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments, wherein:

[0029] Figure 1 : Transmission electron microscope photo of the ultrathin two-dimensional BiVO4-ZnPc1% nanosheet prepared in Example 1;

[0030] Figure 2 : XRD spectrum of the ultrathin two-dimensional BiVO4-ZnPc1% nanosheet prepared in Example 1;

[0031] Figure 3 : Transmission electron microscope photo of the ultrathin two-dimensional BiVO4-ZnPc5% nanosheet prepared in Example 2;

[0032] Figure 4 : XRD spectrum of the ultrathin two-dimensional BiVO4-ZnPc5% nanosheet prepared in Example 2;

[0033] Figure 5 : Transmission electron microscope photo of the ultrathin two-dimensional BiVO4-ZnPc10% nanosheet prepared in Example 3;

[0034] Figure 6 : XRD spectrum of the ultrathin two-dimensional BiVO4-ZnPc10% nanosheet prepared in Example 3;

[0035] Figure 7 : The degradation efficiency of organic pollutants in oil drilling waste fluids prepared in Example 1 and Example 3, as well as the BiVO4 nanosheet samples, changes over time under simulated visible light irradiation;

[0036] Figure 8 :and Figure 7 The corresponding pseudo-first-order kinetic equation fitting results;

[0037] Fig. 9 : Transmission electron microscope photo of the ultrathin two-dimensional BiVO4-ZnPc20% nanosheet prepared in Example 4;

[0038] Fig.10 : XRD spectrum of the ultrathin two-dimensional BiVO4-ZnPc20% nanosheet prepared in Example 4;

[0039] Fig.11 : Transmission electron microscope photo of the ultrathin two-dimensional BiVO4-ZnPc30% nanosheet prepared in Example 5;

[0040] Fig.12: XRD spectrum of the ultrathin two-dimensional BiVO4-ZnPc30% nanosheet prepared in Example 5;

[0041] Fig.13 : Transmission electron microscope photo of the ultrathin two-dimensional BiVO4-ZnPc50% nanosheet prepared in Example 6;

[0042] Fig.14 : XRD spectrum of the ultra-thin two-dimensional BiVO4-ZnPc50% nanosheet prepared in Example 6;

[0043] Fig.15 : The degradation efficiency of 10ppm RhB organic dye under simulated visible light irradiation of large-size ultrathin two-dimensional BiVO4-ZnPc nanosheets and BiVO4 nanosheet samples prepared in Example 1, Example 3, Example 5 and Example 6 varies with time;

[0044] Fig.16 :and Fig.15 The corresponding pseudo-first-order kinetic equation fitting results;

[0045] Fig.17 : Using sodium terephthalate as an indicator, irradiation with a 300W xenon lamp for 5 minutes; conducting fluorescence tests to detect the ability of the photocatalytic material to produce hydroxyl radicals (•OH), comparing its fluorescence intensity at 420nm, and preliminarily detecting its photocatalytic performance;

[0046] Fig.18 : Using 25mgBiVO4-ZnPc10% photocatalytic material, 300W xenon lamp (AM1.5 filter) irradiated 100ml suspension system at 15℃ for 330min, and the stirring speed was 540rad / min to degrade 70mg / L of organic pollutants in petroleum drilling waste liquid. DETAILED DESCRIPTION

[0047] Example 1

[0048] 10 mL of non-coordinating organic solvent octadecene was added with 3 mmol Bi (NO3) 3·5H2O and the same volume of ligand 6 mL oleic acid and 6 mL oleylamine, stirred at 190°C for 10 min in a nitrogen atmosphere and then stopped heating; 1% molar ratio of zinc phthalocyanine ZnPc was dispersed in 4 mL organic solvent dimethyl sulfoxide (DMSO) by ultrasonication for 20 min, stirred for 60 min, and added to the above step and stirred at 100°C for 5 min. Then 10 mL of water, 4 mL of 16 M concentrated nitric acid, and 9.6 mmol NH4VO3 were added and stirred for 5 min, and stirred at 100°C for 60 min in a nitrogen atmosphere. After cooling to room temperature, 10 mL of ethanol was added to remove the lower aqueous solution, and 10 mL of water was added to the upper organic phase to emulsify it to a viscous state. After adding 10 mL of ethanol to break the emulsion, the lower aqueous solution was removed, and the upper clear liquid was removed by centrifugation. 10 mL of n-hexane and 10 mL of ethanol were added, and the BiVO4-ZnPc1% nanocomposite yellow solid powder was obtained by centrifugation and drying. Its mass is about 0.9 g.

[0049] Refer to the instruction manual Figure 1 And the instruction manual Figure 2 The obtained BiVO4-ZnPc1% has a square flake morphology, an average lateral size of 1μm, and a thickness of 2.8nm; it has good monodispersity and presents an obvious ultra-thin nanosheet structure. After the introduction of zinc phthalocyanine into the obtained BiVO4-ZnPc1% nanosheet, two crystal forms of BiVO4 appeared in XRD: one is the monoclinic phase of 75-1866, and the other is the tetragonal phase of 83-1812.

[0050] Example 2

[0051] 10mL of non-coordinating organic solvent octadecene was added with 3mmol Bi (NO3) 3·5H2O and the same volume of ligand 6mL oleic acid and 6mL, stirred at 185℃ for 10min in nitrogen atmosphere and oleylamine, and then stopped heating; 5% molar ratio of zinc phthalocyanine ZnPc was dispersed in 4mL organic solvent dimethyl sulfoxide (DMSO) by ultrasonic for 20min, stirred for 60min, and added to the above mixture and stirred at 90℃ for 4min. Then 10mL of water, 4mL of 15M concentrated nitric acid, and 12mmol NH4VO3 were added and stirred for 15min, and stirred at 100℃ for 60min in nitrogen atmosphere. After cooling to room temperature, 10 mL of ethanol was added to remove the lower aqueous solution, and 10 mL of water was added to the upper organic phase to emulsify it to a viscous state. After adding 10 mL of ethanol to break the emulsion, the lower aqueous solution was removed, and the upper clear liquid was removed by centrifugation. 10 mL of n-hexane and 10 mL of ethanol were added, and the BiVO4-ZnPc5% nanocomposite yellow solid powder was obtained by centrifugation and drying. Its mass is about 0.975 g.

[0052] Refer to the instruction manual Figure 3 And the instruction manual Figure 4 The obtained BiVO4-5%ZnPc has a square flake morphology, an average lateral size of 1μm, and a thickness of 2.5nm; it has good monodispersity and presents an obvious ultra-thin nanosheet structure. After the introduction of zinc phthalocyanine into the obtained BiVO4-ZnPc5% nanosheet, two crystal forms of BiVO4 appeared in XRD: one is the monoclinic phase of 75-1866, and the other is the tetragonal phase of 83-1812.

[0053] Example 3

[0054] 15mL of non-coordinating organic solvent octadecene was added with 3mmol Bi (NO3) 3·5H2O and the same volume of ligand 9mL oleic acid and 9mL oleylamine, stirred at 190℃ for 12min in nitrogen atmosphere and then stopped heating; 10% molar ratio of zinc phthalocyanine ZnPc was dispersed in 4mL organic solvent ethanol by ultrasonic for 20min, stirred for 60min, added to the above mixture and stirred at 100℃ for 5min. Then 15mL of water, 5mL of 16M concentrated nitric acid, and 14.4mmol NH4VO3 were added and stirred for 10min, and stirred at 100℃ for 70min in nitrogen atmosphere. After cooling to room temperature, 15 mL of ethanol was added to remove the lower aqueous solution, and 15 mL of water was added to the upper organic phase to emulsify it to a viscous state. After adding 15 mL of ethanol to break the emulsification, the lower aqueous solution was removed, and the upper clear liquid was removed by centrifugation. 15 mL of n-hexane and 15 mL of ethanol were added, and a yellow solid powder of BiVO4-ZnPc10% nanocomposite material was obtained by centrifugation and drying. Its mass is about 1.085 g.

[0055] Refer to the instruction manual Figure 5 And the instruction manual Figure 6 The obtained BiVO4-ZnPc10% has a square flake morphology, an average lateral size of 1μm, and a thickness of 2.9nm; it has good monodispersity and presents an obvious ultra-thin nanosheet structure. After the introduction of zinc phthalocyanine into the obtained BiVO4-ZnPc10% nanosheet, two crystal forms of BiVO4 appeared in XRD: one is the monoclinic phase of 75-1866, and the other is the tetragonal phase of 83-1812.

[0056] Refer to the instruction manual Figure 7 And the instruction manual Figure 8In the process of degrading organic pollutants in oil drilling waste liquid, BiVO4-ZnPc10% showed the best catalytic performance. 25mg of photocatalytic material BiVO4-ZnPc10% was dispersed in 100mL of oil drilling waste liquid with an organic pollutant concentration of 70mg / L by ultrasonic for 3min to form a suspension system. The condensation temperature was controlled at 15℃ and irradiated for 150min under a 300W xenon lamp (AM1.5 filter) with a stirring speed of 540rad / min. The degradation efficiency reached 54.12%. The ultra-thin two-dimensional BiVO4-ZnPc10% nanosheet showed very excellent performance in degrading organic pollutants in oil drilling waste liquid, and its first-order kinetic reaction rate constant was more than 3 times that of the BiVO4 nanosheet sample.

[0057] Example 4

[0058] 3mmolBi(NO3)3·5H2O and the same volume of ligands 9mL oleic acid and 9mL oleylamine were added to 15mL non-coordinating organic solvent ODE, stirred at 190℃ for 12min under nitrogen atmosphere and then stopped heating; 20% molar ratio phthalocyanine zinc ZnPc was dispersed in 3mL organic solvent ethanol by ultrasonic for 20min, stirred for 60min, added to the above mixture and stirred at 100℃ for 5min. Then 15mL water, 5mL 16M concentrated nitric acid, and 16.8mmol NH4VO3 were added and stirred for 10min, and stirred at 100℃ for 80min under nitrogen atmosphere. After cooling to room temperature, 15 mL of ethanol was added to remove the lower aqueous solution, and 15 mL of water was added to the upper organic phase to emulsify it to a viscous state. After adding 15 mL of ethanol to break the emulsion, the lower aqueous solution was removed, and the upper clear liquid was removed by centrifugation. 15 mL of n-hexane and 15 mL of ethanol were added, and the BiVO4-ZnPc20% nanocomposite yellow solid powder was obtained by centrifugation and drying. Its mass is about 1.2 g.

[0059] Refer to the instruction manual Fig. 9 And the instruction manual Fig.10 The obtained BiVO4-ZnPc20% has a square flake shape, an average lateral size of 500nm, and a thickness of 3nm; it has good monodispersity and presents an obvious ultra-thin nanosheet structure. After the introduction of zinc phthalocyanine into the obtained BiVO4-ZnPc20% nanosheet, two crystal forms of BiVO4 appeared in XRD: one is the monoclinic phase of 75-1866, and the other is the tetragonal phase of 83-1812.

[0060] Example 5

[0061] 15mL of non-coordinating organic solvent octadecene was added with 6mmol Bi (NO3) 3·5H2O and the same volume of ligand 12mL oleic acid and 12mL oleylamine, and stirred for 15min at 190℃ in a nitrogen atmosphere; heating was stopped, and 30% molar ratio of zinc phthalocyanine ZnPc was dispersed in 5mL organic solvent dichloromethane by ultrasonication for 20min, stirred for 70min, and added to the above step and stirred at 110℃ for 6min. Then 15mL of water, 6mL of 16M concentrated nitric acid, and 19.2mmol NH4VO3 were added and stirred for 20min, mixed and stirred for 15min, and stirred at 100℃ for 80min in a nitrogen atmosphere. After cooling to room temperature, 15 mL of ethanol was added to remove the lower aqueous solution, and 15 mL of water was added to the upper organic phase to emulsify it to a viscous state. After adding 15 mL of ethanol to break the emulsification, the lower aqueous solution was removed, and the upper clear liquid was removed by centrifugation. 15 mL of n-hexane and 15 mL of ethanol were added, and a yellow solid powder of BiVO4-ZnPc30% nanocomposite material was obtained by centrifugation and drying. Its mass is about 1.3 mg.

[0062] Refer to the instruction manual Fig.11 And the instruction manual Fig.12 The obtained BiVO4-ZnPc30% has a square flake shape, an average lateral size of 300nm, and a thickness of 2.8nm; it has good monodispersity, uniform size, and presents an obvious ultra-thin nanosheet structure. After the introduction of zinc phthalocyanine into the obtained BiVO4-ZnPc30% nanosheet, two crystal forms of BiVO4 appeared in XRD: one is the monoclinic phase of 75-1866, and the other is the tetragonal phase of 83-1812.

[0063] Example 6

[0064] 20mL of non-coordinating organic solvent octadecene was added with 6mmol Bi (NO3) 3·5H2O and the same volume of ligand 12mL oleic acid and 12mL oleylamine, stirred at 195℃ for 15min in nitrogen atmosphere and then stopped heating; 50% molar ratio zinc phthalocyanine ZnPc was dispersed in 4mL organic solvent dichloromethane (DCM) by ultrasonic for 20min, stirred for 60min, added to the above step and stirred at 100℃ for 5min. Then 20mL water, 6mL 16M concentrated nitric acid and 24mmol NH4VO3 were added and stirred for 20min, and stirred at 105℃ for 90min in nitrogen atmosphere. After cooling to room temperature, 20 mL of ethanol was added to remove the lower aqueous solution, and 15 mL of water was added to the upper organic phase to emulsify it to a viscous state. After adding 20 mL of ethanol to break the emulsion, the lower aqueous solution was removed, and the upper clear liquid was removed by centrifugation. 20 mL of n-hexane and 20 mL of ethanol were added, and a yellow solid powder of BiVO4-ZnPc50% nanocomposite material was obtained by centrifugation and drying. Its mass is about 1.5 g.

[0065] Refer to the instruction manual Fig.13 And the instruction manual Fig.14 The obtained BiVO4-ZnPc50% has a square flake shape, an average lateral size of 400nm, and a thickness of 2.9nm; it has good monodispersity, uniform size, and presents an obvious ultra-thin nanosheet structure. After the introduction of zinc phthalocyanine into the obtained BiVO4-ZnPc50% nanosheet, two crystal forms of BiVO4 appeared in XRD: one is the monoclinic phase of 75-1866, and the other is the tetragonal phase of 83-1812.

[0066] In the process of degrading RhB, BiVO4-ZnPc10% showed the best catalytic performance. 15 mg of photocatalytic material BiVO4-ZnPc10% was dispersed in 100 mL of 10 mg / L RhB aqueous solution by ultrasonic for 3 min to form a suspension system, and then condensed and controlled at 15 °C under irradiation of 300 W xenon lamp (AM1.5 filter) for 60 min, with a stirring speed of 540 rad / min, and its degradation efficiency reached 98.42%.

[0067] Example 7

[0068] Refer to the instruction manual Fig.15 ~Instructions attached Fig.18 , take 100μg / mL BiVO4, BiVO4-ZnPc1%, BiVO4-ZnPc10% nanosheets 2mL, and use 2*10 -3 mM disodium salt of p-benzenedicarboxylic acid was used as the •OH fluorescence detection indicator. After 300W xenon lamp irradiation for 5 minutes, the supernatant was taken for fluorescence test after high-speed centrifugation at 13000rad / min. The peak intensity at 420nm was compared to compare its ability to produce •OH. 25mg of photocatalytic material BiVO4-ZnPc10% was dispersed in 100mL of oil drilling waste liquid with an organic pollutant concentration of 70mg / L by ultrasonic for 3min to form a suspension system. The condensation temperature was controlled at 15℃ and irradiated for 330min under 300W xenon lamp (AM1.5 filter) with a stirring speed of 540rad / min. The degradation efficiency reached 100%, and all organic pollutants in the oil drilling waste liquid could be degraded.

[0069] Ultrathin two-dimensional BiVO4-ZnPc1% nanosheets and BiVO4-ZnPc10% nanosheets exhibit excellent performance in degrading organic dye RhB, and the first-order kinetic reaction rate constant of BiVO4-ZnPc10% is more than 26 times that of BiVO4 nanosheet samples. The addition of ZnPc is conducive to the production of •OH by photocatalytic materials, of which BiVO4-ZnPc1% is 1.46 times that of BiVO4 itself, and BiVO4-ZnPc10% is 1.82 times that of BiVO4 itself.

[0070] In summary, after reading the present invention document, ordinary technicians in this field can make various other corresponding transformation schemes based on the technical scheme and technical concept of the present invention without creative mental labor, which all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a BiVO4-ZnPc nanocomposite material, characterized in that: The following steps are involved: S1. Add 3~6mmol of bismuth source Bi(NO3)3·5H2O, 6~12mL of oleic acid and 6~12mL of oleylamine to 10~20mL of non-coordinating organic solvent, stir at 185~195℃ for 10~15min, and stop heating. S2. Disperse zinc phthalocyanine ZnPc in 3-5 mL of an organic solvent at a molar ratio of 1%-50% compared to Bi(NO3)3, stir for 50-70 min, then add to step S1, and stir at 90-110°C for 4-6 min; S3. Add 10-20 mL of water, 4-6 mL of 15-16 M concentrated nitric acid and 9.6-24 mmol of NH4VO3, mix and stir for 5-20 min, and stir at 100-105°C for 60-90 min under a nitrogen atmosphere; S4. After cooling to room temperature, 10-20 mL of ethanol was added to remove the lower aqueous solution, and 10-20 mL of water was added to the upper organic phase to emulsify it to a viscous state. After adding 10-20 mL of ethanol to break the emulsification, the lower aqueous solution was removed, and the upper clear liquid was removed by centrifugation. 10-20 mL of n-hexane and 10-20 mL of ethanol were added, and BiVO4-ZnPc nanocomposites of different proportions were obtained by centrifugation and drying.

2. The method for preparing a BiVO4-ZnPc nanocomposite material according to claim 1, characterized in that: The content of zinc phthalocyanine ZnPc in step S2 is 10%.

3. The method for preparing a BiVO4-ZnPc nanocomposite material according to claim 1, characterized in that: The content of zinc phthalocyanine ZnPc in step S2 is 30% or 50%.

4. A method for preparing a BiVO4-ZnPc nanocomposite material according to claim 2 or 3, characterized in that: The BiVO4-ZnPc nanocomposite material is in the form of an ultra-thin two-dimensional sheet with a thickness of 2.8-3 nm.

5. The method for preparing a BiVO4-ZnPc nanocomposite material according to claim 1, characterized in that: In the step S1, a bismuth source, oleic acid and oleylamine are reacted under a nitrogen atmosphere.

6. The method for preparing a BiVO4-ZnPc nanocomposite material according to claim 5, characterized in that: The amounts of oleic acid and oleylamine used are the same.

7. The method for preparing a BiVO4-ZnPc nanocomposite material according to claim 6, characterized in that: The non-coordinating organic solvent is octadecene.

8. The method for preparing a BiVO4-ZnPc nanocomposite material according to claim 1, characterized in that: In the step S2, zinc phthalocyanine ZnPc is dispersed in an organic solvent by ultrasonication for 20 minutes.

9. The method for preparing a BiVO4-ZnPc nanocomposite material according to claim 8, characterized in that: The organic solvent in step S2 is dimethyl sulfoxide, ethanol or dichloromethane.

10. The method for preparing a BiVO4-ZnPc nanocomposite material according to claim 1, characterized in that: The drying in step S4 specifically refers to oven drying.

Citation Information

Patent Citations

  • Morphology-controllable BiVO4 nanocrystal preparation method with 'two-phase method'

    CN108892170A

  • Preparation method and application of ultrathin two-dimensional metal phthalocyanine / bismuth vanadate composite photocatalyst

    CN109939744A

  • Photocatalyst carrying carrier and manufacturing method therefor

    JP2004181276A